Analisis Pengaruh Customer Journey Mapping Dalam Perancangan Customer Retention Pada E-commerce Shopee Menggunakan Metode Service Quality - Derezky Elvaberta Djami; Sintaria Sembiring (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2023)
Technological developments accompanied by increasing population growth rates in Indonesia affect people's lives in meeting their daily needs. With e-commerce that is present as an innovation in the use of technology and internet network assistance, it makes it easier for people to buy and sell goods online. Shoppe is one of the e-commerce with the most sales and visitors in Indonesia as of 2022 according to a national survey conducted by BOI Research. This research was conducted to analyze and provide information about the influence of the customer journey map consisting of the stages of discovery, use, and loyalty with 5 dimensions of service quality Service Quality Method which includes reliability, responsiveness, assurance, empathy, and tangibles on customer strategy design retention on Shopee e-commerce. The results of this study obtained the results that there is a positive relationship between the discovery and use process on customer loyalty in making purchases. Companies can evaluate this stage in designing strategies to gain customer trust and loyalty in order to make repeat purchases.